PENGARUH TERPAAN BERITA KECELAKAAN PESAWAT LION AIR JT 610 DI MEDIA INTERNET TERHADAP CITRA JASA PENERBANGAN LION AIR (Survei Pada Pengguna Jasa Penerbangan di Bandara Sultan Syarif Kasim II Pekanbaru) - Yaumil Fitri Zen; Anuar Rasyid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
In late 2018, the news about Lion Air JT 610 crash is one of the most talked news in internet. This fast spreading of information have some effects. Therefore, news exposure about Lion Air JT610 plane crash can affect the image of Lion Air. The purpose of this research is to prove whether there is effect of Lion Air JT610 plane crash news exposure on internet towards the image of Lion Air or not. The method used in this research is explanatory quantitative. Data collection techniques are done by questionnaire and documentation. The population in this research are the airline consumers at Sultan Syarif Kasim II Airport Pekanbaru. This research used accidental sampling towards the respondents. To know the impact of two variable used in this research, the researcher used simple linear regression analysis. Questionnaire data processing is conducted with Statistic Product and Service Solution SPSS for Windows version 16.  Based on the result of simple linear regression in this research, regression coefficient is Y= 26,676 + 0,216 X with significance level 0,03 and smaller than  = 0,05. Based on determination test the result is 4,9% which means there is a very weak effect of Lion Air JT610 crash news exposure on internet towards the image of Lion Air airline at Sultan Syarif Kasim II airport Pekanbaru.